Analisis Manajemen Risiko Aktivitas Pengadaan pada Percetakan Surat Kabar - Adi, Deshtyan Erlangga; Susanto, Novie (Metris: Jurnal Sains dan Teknologi, 2017)
Risk management is a management effort to control risk the company's operational activities by conducting risk analysis, risk evaluation and its mitigation plan. Risk management efforts are feasible to be applied into the business activities of the company including the procurement activities. PT Masscom Graphy is a printing company that its main request is printing Suara Merdeka newspaper. Since June 2016, there has been a decrease in demand of 27,000 copies of Suara Merdeka newspapers which resulted in disruption of the company's cash flow. It responded by the company by applying a tight money policy on every company activity including procurement activities. Such policies increase the risks that may occur, so that risk management efforts are needed to minimize the impact that can occur. The House of Risk method is used to identify risk events and the risk agents that cause them, and to design mitigation actions to address those risk agents. The results showed that there were 13 risk events and 17 identified risk agents, with the priority risk agents to be addressed were A2 risks (no contracts formed with suppliers) and A14 (application of the same procurement strategy to each raw material). Recommended mitigation actions are (1) review of contract system, (2) differentiation of procurement strategy, (3) mapping of raw material characteristics, and (4) supplier performance evaluation.